Kegiatan Refleksi Modul Nusantara Sebagai Wadah Implementasi Nilai Kebhinekaan Mahasiswa PMM Inbound Polibatam - Feby, Feby; Havwini, Tiam; Fadilah, Nurul; Sari, Desi Ratna; Firdaus, Fadli (Prodi PPKn ULM dan AP3KnI Kal-Sel, 2024)
This study aims to examine the reflection activities of Modul Nusantara as a medium for implementing Kebhinekaan values of PMM Inbound Students at Polibatam. The research utilizes a descriptive qualitative method. The sample consists of 6 inbound PMM students from Polibatam in 2024, grouped into 3 different cohorts. Data collection was conducted through documentation and observation. The documentation data was sourced from the weekly reports of students regarding the reflection sub-activities. The results indicate that the reflection activities of Modul Nusantara serve as a medium for the implementation of Kebhinekaan values among inbound PMM students at Polibatam. These reflection activities help students understand and appreciate the values of Kebhinekaan. The implementation of Kebhinekaan values in these student activities not only enrich cultural insights but also strengthen the foundation of unity amidst various differences. As the next generation, students must remain active in preserving and maintaining Kebhinekaan that characterizes Indonesia.